Evaluation of the Efficacy and Complications of Different Hysterectomy Techniques in the Management of Uterine Fibroids - Pranshi Asati; Swati Asati; Varsha Sinha; Heena Dixit; Akriti Mahajan; Yasser Khalid Alraddadi; Afroz Kalmee Syed (Wolters Kluwer Medknow Publications, 2024)
Introduction: Uterine fibroids, which are benign tumors affecting a significant proportion of women, often necessitate hysterectomy for suggestive relief. Understanding the relative efficiency and safety profiles of different techniques is crucial for optimizing patient care. Materials and Methods: This prospective cohort study enrolled women diagnosed with symptomatic uterine fibroids who underwent hysterectomy. Surgical techniques included "total abdominal hysterectomy (TAH)", "laparoscopic hysterectomy (LH)", and "vaginal hysterectomy (VH)". Efficacy outcomes included operative time, blood loss, and recurrence rates, while complications encompassed intraoperative and postoperative adverse events. Results: Laparoscopic hysterectomy demonstrated the shortest operative time and least blood loss compared with TAH and VH. Total abdominal hysterectomy had the highest rates of both intraoperative and postoperative complications, followed by LH and VH. Recurrence rates were comparable among the three techniques. Conclusion: Laparoscopic hysterectomy offers advantages in operative efficiency and complication rates compared with total abdominal and vaginal hysterectomy techniques.